PENILAIAN KINERJA UNIT PELAYANAN PADA ORGANISASI PUBLIK - Ismiyarto Ismiyarto (Institut Pemerintahan Dalam Negeri, 2017)
Public policy to assess the performance of public services has been regulated in Law Number 25 Year 2009 on Public Service, Government Regulation No. 96 Year 2012 on Implementation of Law Number 25 Year 2009 on Public Service. Technically regulated in the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 38 of 2012 on Guidelines for Assessment of Performance of Public Service Units. Various performance appraisal policies of public service units in public organizations need to be continuously socialized and applied within the Ministry/ Institution/Government environment. Given such an assessment it strongly encourages the innovation of various types of public services to create better public services over time. With the realization of a better public service this is one of the goals of bureaucracy reform.